Peculiarities of the clinical course and pathomorphological picture of ovarian endometriosis and adenomyosis in reproductive aged women - I.Z. Hladchuk; N.M. Rozhkovska; V.O. Sytnikova; I.V. Shpak; S.M. Syvyi (Publishing House TRILIST, 2022)
Оbjectives: to assess the clinical and pathomorphological features of ovarian endometriosis and adenomyosis in women of reproductive age in order to determine possible causes of fertility disorders and ways to correct them. Materials and methods. 87 patients were examined and divided into 2 groups. The first group included 45 (51.7%) patients with adenomyosis with or without concomitant pathology. The second group included 42 (48.3%) women with ovarian endometriomas. The control group consisted of 30 healthy women of childbearing age who were screened for male infertility. Results. Clinical examination of the patients revealed a high frequency of gynecological (uterine fibroids, endometrial hyperplasia, infertility) and extragenital pathology. Obstetric and gynecological history was burdened by reproductive losses (involuntary and medical abortions, ectopic pregnancy), premature birth, preeclampsia, abnormal uterine and obstetric bleeding, and pelvic surgery. All patients underwent endoscopic treatment (laparoscopy, hysteroscopy). Morphological examination revealed features of the structure of endometrioid cysts, which explains the decrease in ovarian reserve, active adenomyosis, reactive hyperplasia and chronic endometritis, distortion of the uterine cavity by fibroids. This may play an important role in implantation and placentation. Conclusions. Features of morphogenesis of ovarian endometrioma, found by us cystic and glandular-cystic forms may form the basis of endometrial microperforation pathogenesis, development of adhesions of the pelvic organs (in every third woman), ectopic pregnancy, fibrotic adjacent endometrioid tissue and reduction of ovarian reserve. The peculiarities of the uterus histostructure in adenomyosis, frequent combination with uterine fibroids, endometrial hyperplasia, chronic endometritis, ovarian endometriosis, deep infiltrative endometriosis, old age, aggravated obstetric anamnesis and the history of obstetric disorders may be related.